Pengaruh Supervisi Akademik, Kompetensi Padagogik, Kompetensi Kepribadian, Kompetensi Sosial Terhadap Kinerja Guru PAI Dimediasi Workplace Spirituality di SMA Negeri Se-Kabupaten Kediri - Khoirotul Izzah; Munirul Abidin (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
The purpose of this study is to find out 1) How effective is the implementationof academic supervision, 2) How effective is pedsgogic competence,3)personality competence,4)social competence on 5)PAI teacher performance in mediation 6)workplace spirituality The influence of academic supervision, pedagogic competence, personality competence, competence 4)social competence on 5)P AI teacher performance in mediation 6)workplace spirituality in high schools in Kediri district. This study used quantitative methods with a population of 40 and a research sample of 50 respondents. Data collection techniques use questionnaires. The results showed that there was 1) The effectiveness of academic supervision on the performance of PAI teachers in Kediri district is classified as less strong than the overall data showing that workplace spirituality cannot moderate the relationship between academic supervision and teacher performance, but from the overall data workplace spirituality can moderate the relationship between competencies Social and teacher performance.